PERGESERAN FUNGSI PERAHU BAGANDUANG PADA UPACARA TRADISIONAL DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Puligus, Darcolis Puligus Darcolis; Saiman, Marwoto Saiman Marwoto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Indonesia is a pluralistic, diverse, and pluralistic society it is a country of more than 500 tribes united by a national system as a nation in the container Indonesian National Culture. Cultural diversity one of which is seen in ceremony Melayu Riau have an open culture and accommodating and adaptive system of religious values and customs and traditions are contained. Cultural traditions that developed from various districts in Riau province is very much. Among them are cultural traditions Begandung boat coming from various regions, including in Kuantan Singingi. Bagandung boat is a culture of the village opposite the beach District Kuantan Mudik, which has evolved from ancient times to the present. This culture is celebrated every year at the feast of Eid al-Fitr point is to purify themselves from calamity and distress. The purpose of this study was to determine the background of the boat beganduang in Kuantan Mudik District Kuantan Singingi, to know the process of making a boat baganduang in Kuantan Mudik District Kuantan Singingi, to know the function of the boat baganduang in Kuantan Mudik District Kuantan Singingi, to know the process of shifting the functions of the boat baganduang in Kuantan Mudik District Kuantan Singingi, to know the impact of the shift function baganduang boat in Kuantan Mudik District Kuantan Singingi. The method used in this study is the historical method and qualitative methods. Data were obtained from interviews and analyzed in its own language. The research location is in Kuantan Mudik District Kuantan Singingi. When the study started from the seminar proposal to the Thesis exam. Data collection techniques used are observation, interview techniques, technical documentation and technical literature. Results from this research that the shift function baganduang boat visible from disuse boat baganduang as a means but only as a lime manjampuik festival alone. This shift is due to many factors that accompany it, and indeed it is proper to shift according to the changing times. The shift function baganduang boat not only on its usefulness, but also the values contained in the boat baganduang also shifted as the aesthetic value and the value of its mythological.Keywords: Shift, Function, Boat Baganduang